Asian monsoon climate during the Last Glacial Maximum: palaeo‐data–model comparisons. (16th July 2013) - Chabangborn, Akkaneewut; Brandefelt, Jenny; Wohlfarth, Barbara
<x xml:space="preserve">Abstract</x> The Last Glacial Maximum (LGM) (23–19 ka BP) in the Asian monsoon region is generally described as cool and dry, due to a strong winter monsoon. More recently, however, palaeo‐data and climate model simulations have argued for a more variable LGM Asian monsoon climate with distinct regional differences. We compiled, evaluated, and partly re‐assessed proxy records for the Asian monsoon region in terms of wet/dry climatic conditions based on precipitation and effective moisture, and of sea surface temperatures. The comparison of the palaeo‐data set to LGM simulations by the Climate Community System Model version 3 (CCSM3) shows fairly good agreement: a dry LGM climate in the western and northern part due to a strengthened winter monsoon and/or strengthened westerly winds and wetter conditions in equatorial areas, due to a stronger summer monsoon. Data–model discrepancies are seen in some areas and are ascribed to the fairly coarse resolution of CCSM3 and/or to uncertainties in the reconstructions. Differences are also observed between the reconstructed and simulated northern boundaries of the Intertropical Convergence Zone (ITCZ). The reconstructions estimate a more southern position over southern India and the Bay of Bengal, whereas CCSM3 simulates a more northern position. In Indochina, the opposite is the case. The palaeo‐data indicate that climatic conditions changed around 20–19 ka BP, with some regions receiving higher precipitation and some experiencing drier conditions, which would imply a distinct shift in summer monsoon intensity. This shift was probably triggered by the late LGM sea‐level rise, which led to changes in atmosphere–ocean interactions in the Indian Ocean. The overall good correspondence between reconstructions and CCSM3 suggests that CCSM3 simulates LGM climate conditions over subtropical and tropical areas fairly well. The few high‐resolution qualitative and quantitative palaeo‐records available for the large Asian monsoon region make reconstructions however still uncertain.